2018
DOI: 10.1177/1747493018772747
|View full text |Cite
|
Sign up to set email alerts
|

Stroke care in Africa: A systematic review of the literature

Abstract: Background Appropriate systems of stroke care are important to manage the increasing death and disability associated with stroke in Africa. Information on existing stroke services in African countries is limited. Aim To describe the status of stroke care in Africa. Summary of review We undertook a systematic search of the published literature to identify recent (1 January 2006-20 June 2017) publications that described stroke care in any African country. Our initial search yielded 838 potential papers, of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 53 publications
5
60
1
Order By: Relevance
“…Regarding The average prehospital delay for patients with IS in Morocco has ranged between 26 to 61.9 hours, which far exceeds the therapeutic window recommended by randomized clinical trials [65].This finding is in accordance with the median admission time (31 hours) mentioned in a review of literature on the African continent [66]. In addition, it joins the average consultation time mentioned in a prospective cross-sectional study conducted at the University Hospital Center of Brazzaville in the Republic of Congo, where they have reported a period of 28.2 hours [67].…”
Section: The Percentage Of Patients With Thrombolyzed Ischemic Strokesupporting
confidence: 78%
See 1 more Smart Citation
“…Regarding The average prehospital delay for patients with IS in Morocco has ranged between 26 to 61.9 hours, which far exceeds the therapeutic window recommended by randomized clinical trials [65].This finding is in accordance with the median admission time (31 hours) mentioned in a review of literature on the African continent [66]. In addition, it joins the average consultation time mentioned in a prospective cross-sectional study conducted at the University Hospital Center of Brazzaville in the Republic of Congo, where they have reported a period of 28.2 hours [67].…”
Section: The Percentage Of Patients With Thrombolyzed Ischemic Strokesupporting
confidence: 78%
“…This could also be explained by the fact that most of the patients arrived at the emergency rooms using personal or common means of transportation (taxi, personal car), and only a minority used ambulance services (3.5%) [24]. From same perspective, a recent review demonstrated that low awareness of the signs and symptoms of stroke, the shortage of medical transportation, health care staff and stroke management units, as well as the economic cost of the access to brain imaging facilities and thrombolysis were reported as major obstacles to improve stroke care and stroke management in Africa [66].…”
Section: The Percentage Of Patients With Thrombolyzed Ischemic Strokementioning
confidence: 99%
“…Consequently, insufficient knowledge of risk factors, warning signs, and urgent therapeutic approach options have been identified as a serious cause of increased mortality and morbidity due to stroke [ 7 ]. Similarly, this knowledge deficiency has been identified as one of the significant barriers to accessing quality health care for stroke in Africa, as well as a factor affecting pre-hospital time [ 8 9 ]. Several studies in various countries have all confirmed the persistence of a low level of knowledge among the general public about stroke, and more specifically about risk factors and warning signs [ 10 11 12 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other resource‐poor regions, recent research indicates access and delivery of quality and evidence‐based stroke care in Africa is limited and often poor . Studies in Ghana, Senegal and Congo further exemplify the limited nature of access to quality and evidence‐based stroke care in LMICs.…”
Section: Introductionmentioning
confidence: 95%
“…8 Similar to other resource-poor regions, recent research indicates access and delivery of quality and evidence-based stroke care in Africa is limited and often poor. 3,4,[8][9][10] Studies in Ghana, 5 Senegal 6 and Congo 7 further exemplify the limited nature of access to quality and evidence-based stroke care in LMICs. Efforts to improve uptake of better stroke care interventions to ensure optimal patient outcomes in resource-poor settings have been persistently hampered by a range of barriers such as lack of skilled health personnel, patients' lack of funds to meet health-care costs and inadequate health infrastructure.…”
Section: Introductionmentioning
confidence: 99%